Toxoplasmosis and mental retardation: report of a case-control study - Waleska T. Caiaffa; Clea A. Chiari; Ana R. P. Figueiredo; Fernando Orefice; Carlos M. F. Antunes (Memorias do Instituto Oswaldo Cruz, 1993)
A case-control study evaluating the association between mental retardation and toxoplasmosis was conducted among 845 school children in Belo Horizonte, MG, Brazil. Cases (450) were mentally retarded children attending a public school for special education. Controls (395) were children from the regular public school system. Clinical and anthropometric examinations and interviews were carried out to determine risk factors for toxoplasmosis and mental retardation. Diagnosis of Toxoplasma gondii infection was based upon an indirect immunofluorescent test (IFA); 55% of cases and 29% of controls were positive. The Relative Odds of mental retardation in children with positive serology was 3.0 (95% CI 2.2-4.0). Maternal exposure to cats and contact with soil were associated with an increased risk of mental retardation. Retinochoroiditis was fourfold more prevalent among cases than controls and was only diagnosed in T. gondii IFA positive participants. Congenital toxoplasmosis, in its subclinical form, appears to be an important component in the etiology of mental retardation, especially in high risk (lower socio-economic) groups. The population attributable risk was estimated as 6.0 - 9.0%, suggesting the amount of mental retardation associated with this infection.